Rural road reverse engineering using BIM: an Italian case study - Abbondati, Francesco; Oreto, Cristina; Viscione, Nunzio; Biancardo, Salvatore Antonio (International Conference “Environmental Engineering”, 2020)
The use of Building Information Modeling (BIM) is changing the way to perceive, manage and maintain any infrastructural project. The concept of Smart Roads relaunches the transport infrastructure sector through the digital transformation, able to create lean, quality, safer and cheaper infrastructures. The reverse engineering parametric modeling process was applied to “SS18 VAR” rural road, one of the main viabilities in Southern Italy. The case study was developed in according to the following steps: a) creating Digital Terrain Model (DTM); b) modeling horizontal alignment-vertical profiles; c) modeling 3D Corridor; d) modeling Viaducts; e) creating realistic 3D rendering. Bentley Systems software ® were used in this study. The case study provided interesting elements to evaluate the advantages and disadvantages of design practice through BIM style tools, as well as the current state of the methodology itself.
Keywords: Infrastructure-Building Information Modelling (I-BIM); parametric modelling; viaducts, real world context; smart roads; Southern Italy